MANIFESTING GENDER EQUALITY ON INDONESIAN FEMALE LABOR PARTICIPATION IN MANAGERIAL POSITIONS - Muara Setyanti, Axellina; Finuliyah, Firdaus; Rafliansyah, Muhammad Dzaky; Kesuma, Rian Surya (Jurnal Studi Gender dan Anak, 2024)
Recently, there has been a growing concern for gender equality, especially in women's participation in the labor market, as an effort toward achieving the SDGs. This study aims to explore gender equality regarding women's participation in managerial positions in Indonesia. It uses provincial-level data covering 2018 to 2023. Cluster analysis is applied to assess gender equality through women's representation in managerial roles across different provinces. Additionally, Panel Corrected Standard Error (PCSE) regression is used to analyze provincial-level data, focusing on the socio-economic determinants influencing women's managerial participation. This study found that most provinces in Indonesia are still in the 'low' cluster in terms of women's participation in managerial positions. The panel data analysis reveals that female educational attainment and women's participation in politics significantly enhance women's representation in managerial positions across Indonesian provinces, while the female labor force participation rate also has a positive but less pronounced effect. Economic factors such as GRDP per capita and average labor wage do not show significant impacts, suggesting that non-economic barriers might be more influential in determining women's managerial roles. Overall, the findings highlight the importance of education, political empowerment, and broader female workforce participation in promoting gender equality. Keywords:  Gender Equality, Female Labor Participation, Managerial Position Abstrak Baru-baru ini, terdapat kepedulian yang semakin meningkat terhadap kesetaraan gender, terutama dalam partisipasi perempuan di pasar tenaga kerja, sebagai upaya untuk mencapai SDGs. Penelitian ini bertujuan untuk mengeksplorasi kesetaraan gender terkait partisipasi perempuan dalam posisi manajerial di Indonesia. Data tingkat provinsi yang digunakan mencakup tahun 2018 hingga 2023. Analisis klaster diterapkan untuk mengukur kesetaraan gender melalui representasi perempuan dalam peran manajerial di berbagai provinsi. Selain itu, digunakan regresi Panel Corrected Standard Error (PCSE) untuk menganalisis data tingkat provinsi, dengan fokus pada determinan sosial-ekonomi yang mempengaruhi partisipasi perempuan dalam posisi manajerial. Penelitian ini menemukan bahwa sebagian besar provinsi di Indonesia masih berada pada cluster 'rendah' dalam partisipasi wanita pada posisi managerial. Analisis data panel menunjukkan bahwa pencapaian pendidikan perempuan dan partisipasi perempuan dalam politik secara signifikan meningkatkan representasi perempuan dalam posisi manajerial di seluruh provinsi di Indonesia, sementara tingkat partisipasi angkatan kerja perempuan juga memiliki dampak positif tetapi tidak terlalu besar. Faktor ekonomi seperti PDRB per kapita dan upah tenaga kerja rata-rata tidak menunjukkan dampak yang signifikan, yang menunjukkan bahwa hambatan nonekonomi lebih berpengaruh dalam menentukan peran manajerial perempuan. Secara keseluruhan, temuan tersebut menyoroti pentingnya pendidikan, pemberdayaan politik, dan partisipasi angkatan kerja perempuan yang lebih luas dalam mempromosikan kesetaraan gender. Kata Kunci: Kesetaraan Gender, Partisipasi Tenaga Kerja Wanita, Posisi Manajerial